Preliminary studies on the performance and productivity indices of N'Dama and West African Shorthorn cattle in Ghana - Tuah, A.K.; Danso, Y.N. (Springer, 1985)
The performance of N'Dama and West African Shorthorn cattle in the humid forest zone of Ghana was evaluated using records (1969-1970) from UST livestock farm. The mean age at first calving for N'Dama was 32.07 months. Calving intervals of 501.92 and 462.83 days were obtained for N'Dama and West African Shorthorn. Average birth weight for the two breeds was not significantly affected by breed, season of birth, weight and age of dam. Sex significantly affected the birth weight of the N'Dama calves. Pre-weaning and post-weaning growth rates of N'Dama male calves were significantly greater than the pre-weaning and post-weaning growth rates of females. For the West African Shorthorn sex did not significantly (P>0.05) affect these traits. Calf mortality for the two breeds were 10.53% for N'Dama and 21.05% for the West African Shorthorn. The productivity indices per cow per year were 72.7 kg for N'Dama and 32.1 kg for the West African Shorthorn. The productivity indices per 100 kg cow maintained per year were 36.8 kg for N'Dama and 16.6 kg for the West African Shorthorn.